Model creative problem solving: Kajian efektivitas terhadap kemampuan pemecahan masalah matematis - Nisa, Yuniar Rohmatun; Sari, Indah Puspita; Linda, Linda (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2025)
This research aims to evaluate the effectiveness of the Creative Problem Solving (CPS) learning model on the mathematical problem-solving abilities of junior high school students. The research method employed was an experimental design with pre-test and post-test control group. The students were divided into two groups, namely the experimental group illustrating the comparison between the experimental and control groups before and after the treatment. An instrument for testing mathematical problem-solving abilities was used to collect data before and after the treatment. The results of data analysis showed a significant improvement in mathematical problem-solving abilities in the experimental group after the implementation of the CPS learning model. Therefore, it can be concluded that the Creative Problem Solving learning model effectively enhances the mathematical problem-solving abilities of junior high school students. These findings have positive implications for the development of the mathematics curriculum in junior high schools by emphasizing the importance of integrating learning models that encourage creativity and analytical thinking. Additionally, the results of this research can serve as a foundation for educators and policymakers in designing more innovative teaching strategies to enhance the quality of mathematics education at the junior high school level.